2011
DOI: 10.1002/dc.21649
|View full text |Cite
|
Sign up to set email alerts
|

FNA in diagnosis of orbital lesions causing proptosis in adults

Abstract: The orbit is affected by a wide range of pathologic lesions, for which a morphologic diagnosis is needed to allow adequate therapy. With increasing use of fine needle aspiration (FNA) in diagnostic pathology, the procedure has been applied for the diagnosis of space occupying lesions of the orbit. We present the cytomorphological diagnosis on orbital FNA in adult patients presenting with proptosis. Records of seven adult patients who had presented with proptosis and had undergone orbital FNA were retrieved and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is a valuable procedure for preoperative assessment of the lesions. Various studies have shown the diagnostic accuracy of orbital FNAC range between 72 and 100% (Table ) . A low diagnostic concordance rate was reported, mostly in the initial days of orbital FNAC; whereas more recent and larger studies have shown consistently better results with an overall diagnostic accuracy of 100% .…”
Section: Discussionmentioning
confidence: 99%
“…It is a valuable procedure for preoperative assessment of the lesions. Various studies have shown the diagnostic accuracy of orbital FNAC range between 72 and 100% (Table ) . A low diagnostic concordance rate was reported, mostly in the initial days of orbital FNAC; whereas more recent and larger studies have shown consistently better results with an overall diagnostic accuracy of 100% .…”
Section: Discussionmentioning
confidence: 99%
“…[9101112131516] The main limitations of the procedure include varying sensitivity, nondiagnostic aspirates and possible complications such as retrobulbar haemorrhage, blindness, motility disturbances, ptosis and globe perforation with vitreous haemorrhage. [17] In orbital mass lesions, the diagnostic accuracy of FNAC varies from 23% to 100%, depending on the skill of the operator, size and site of the lesion, and the expertise of the cytopathologist in interpreting the smears.…”
Section: Discussionmentioning
confidence: 99%
“…The most important clinical variables are the age of the patient and medical history [3], which can either suggest or exclude certain diagnoses (for example, cystic lymphangiomas are more likely to manifest themselves at a young age; more patients with orbital pseudotumors may have swollen eyelids, conjunctival congestion, pain, retinal folds or hemorrhage and optic nerve atrophy than patients with lymphoid tumors [4]). The first diagnostic step after clinical examination is represented by imaging techniques.…”
Section: Discussionmentioning
confidence: 99%